Ecology of grazing lawns on tallgrass prairie - Shaffer, Monica (Kansas State University, 2019)
A key feature of many grass-dominated ecosystems is the formation of grazing lawns, distinct patches characterized by intense grazing by mammalian herbivores and a dense short-statured grass canopy. A central concept of grazing lawns is the positive feedbacks between grazing animals and the grass resource. Intraspecific morphological plant trait changes and differences in plant species composition could both or individually play a role in the differences in characteristics of grazing lawns and neighboring tallgrass swards. I studied grazing lawns in North American tallgrass prairie to: a) test the ‘architectural shift hypothesis’ where continued grazing leads to changes in plant architecture resulting in more efficient foraging for grazers, creating a positive feedback that increases grazing and b) examine soil resource (nutrient and water) availability and grass nutritive quality on and off lawns to test the nutrient- and water-based pathways for grazing lawn maintenance. In a separate study (not reported here), we a) examined plant community structure on and off lawns to determine whether species composition differences account for the distinct grazing lawn characteristics and b) assessed effects of grazing lawn formation on tallgrass prairie plant species diversity. Several differences in morphological traits between dominant grasses on grazing lawns and tallgrass swards support the architectural shift hypothesis. For Sorghastrum nutans, Dichanthelium oligosanthes, and Pascopyrum smithii, leaf-to-stem ratio was twice as high on grazing lawns compared to surrounding matrix tallgrass vegetation and tiller branching was higher and culm internode lengths were shorter on grazing lawns for these species. However, Andropogon gerardii traits did not differ between grazing lawns and tallgrass vegetation. For all four species, above-ground tiller biomass and number of below-ground buds were both higher on grazing lawns. Overall, these morphological responses resulted in a higher grass canopy density (forage biomass per unit canopy volume) on grazing lawns and this increased grass canopy density in turn results in higher grazer foraging efficiency by increasing the amount of forage intake per bite and per unit time. D. oligosanthes, P. smithii, and S. nutans plants on grazing lawns had a significantly lower carbon-to-nitrogen ratio and higher nitrogen content than plants in the matrix tallgrass vegetation, while A. gerardii showed no significant difference in nitrogen content or in carbon-to-nitrogen ratio between grazing lawns and surrounding matrix tallgrass vegetation. With regards to the total grass canopy (all grass species combined), nitrogen content was significantly higher on grazing lawns compared to tallgrass vegetation for all three field seasons, 2016, 2017, and 2018. All measured soil nutrients, ammonium, nitrate, phosphorus, and sodium, were significantly higher on grazing lawns compared to soils of surrounding tallgrass swards, while water content showed no significant difference between grazing lawns and surrounding tallgrass vegetation. The results of this study strongly indicate that developmental and morphological shifts result in increased forage density and increased grazing efficiency on grazing lawns and that the frequent and intense activities of large grazers result in increased plant nitrogen content and lower C:N ratios in grasses on tallgrass prairie grazing lawns. Thus, at least two different mechanisms, plant architectural shifts and the nutrient-based pathway could both contribute to the positive feedbacks that encourage further grazing on lawns and grazing lawn maintenance on tallgrass prairie.
Keywords: Grazing lawns; Bison; Tallgrass prairie; Plant traits; Morphological